Efektivitas Pelaksanaan Penghentian Penuntutan Dalam Perkara Tindak Pidana Ringan Berdasarkan Peraturan Kejaksaan No.15 tahun 2020 - Meliana Hutabarat Meliana Hutabarat; Janpatar Janpatar Simamora (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the effectiveness of the implementation of the termination of prosecution for minor criminal cases based on Public Prosecutor Regulation Number 15 of 2020 using a restorative justice approach. The issuance of this regulation is a response to the weaknesses of the formal criminal justice system, which often results in case backlogs, budget inefficiencies, and minimal redress for victims. The methodology used in this paper is a normative juridical legal approach, which includes a review of laws and regulations, doctrines, and related literature. The results of the study indicate that the mechanism of termination of prosecution through restorative justice offers a more humane, fast, simple, and affordable case resolution option. Substantively, this approach has proven effective in restoring relationships between perpetrators, victims, and the community, as well as reducing the potential for recidivism. However, the effectiveness of its implementation is still affected by several obstacles, such as limited technical regulations, resistance from law enforcement officials, and a lack of public understanding. Therefore, strengthening implementation guidelines, increasing prosecutorial capacity, and synergy between law enforcement agencies are essential. Overall, Public Prosecutor Regulation Number 15 of 2020 represents a significant innovation in the effort to realize a more adaptive, efficient, and effective criminal justice system.